Shipboard ADCP current measurements (75 kHz) during RV METEOR cruise M206 - Robert Kopte; Andrea Koschinsky; Rami Kalfouni (PANGAEA, 2025)
Current velocities of the upper water column along the cruise track of R/V Meteor cruise M206 were collected by a vessel-mounted 75 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 5.0 m below the water line. The instrument was operated in narrowband mode (WM10) with a bin size of 8.00 m, a blanking distance of 4.00 m, and a total of 100 bins, covering the depth range between 17.0 m and 809.0 m. Attitude data from the ship extquotesingles motion reference unit were used by the data acquisition software VmDAS internally to convert ADCP beam velocities to geographic coordinates. The Python toolbox OSADCP (version 2.0.2) was used for data post-processing. Acoustic Interferences were identified based on outliers in the ADCP echo intensity data. Echo intensity data were cleaned accordingly and affected velocity cells were flagged to be removed prior ensemble-averaging. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Navigation Satellite System (GNSS), taking into account lever arms of ADCP transducer and GNSS antenna. Accuracy of the derived water velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline.Data processing included water track calibration of the misalignment angle (-46.3362° +/- 0.6125°) and scale factor (1.0051 +/- 0.0113) of the measured velocities. The velocity data were averaged in time using an average interval of 60 s. Depth cells with ensemble-averaged percent-good values below 25% are marked as extquotesinglebad data extquotesingle.